Crossword Puzzle Learning Media to Improve Mastery of Indonesian Vocabulary in Elementary School - Riris Nurkholidah Rambe; Riska Tiara Putri (Jurnal Ilmiah Sekolah Dasar, 2023)
The use of learning media in the teaching and learning process is very important. This can help in creating an effective teaching and learning situation. This study aims to analyze the effect of Crossword Puzzle learning media in increasing elementary school students' Indonesian vocabulary knowledge. This article is a quantitative study using a quasi-experimental approach. The research sample was class IV, totaling 38 students. The 38 students were divided into 2 groups, namely 20 experimental classes and 18 control classes. The selected research instrument is a test in the form of pretest questions and posttest questions that will be given to students. While data analysis uses 2 prerequisite tests, namely the homogeneity test and the normality test. Normality test, data is tested using Shapiro Wilk. While the homogeneity test can be carried out by testing the homogeneity of variants in the IBM SPSS 20 software. Then data analysis is continued with statistical analysis of the t test, namely the paired sample t-test. The research results found that there was an influence of the Crossword Puzzle learning media on increasing elementary school students' mastery of Indonesian vocabulary. It was concluded that the Crossword Puzzle learning media could improve elementary school students' mastery of Indonesian vocabulary.